Predictors of venous thromboembolism in patients with COVID‐19 in an underserved urban population: A single tertiary center experience. (28th April 2021) - Barnes, Drew H.; Lo, Kevin Bryan; Bhargav, Ruchika; Gul, Fahad; DeJoy, Robert; Peterson, Eric; Salacup, Grace; Pelayo, Jerald; Albano, Jeri; Azmaiparashvili, Zurab; Rangaswami, Janani; Carpio, Andres Mora; et al.
Abstract: Introduction: Venous thromboembolism (VTE) is reported in up to 27% of patients with COVID‐19 due to SARS‐CoV‐2 infection. Dysregulated systemic inflammation and various patient traits are presumed to underlie this anomaly. Optimal VTE prophylaxis in COVID‐19 patients has not been established due to a lack of validated models for predicting VTE in this population. Our study aims to address this deficiency by identifying demographic and clinical characteristics of COVID‐19 patients associated with increased VTE risk. Methods: This study is a retrospective analysis of all adult patients (final sample, n = 355) hospitalized with confirmed COVID‐19 at Einstein Medical Center Philadelphia between March 1 and April 24, 2020. Demographic and clinical patient data were collected and factors associated with VTE were identified and analyzed using t‐tests, multivariable logistic regression, and receiver operating characteristic (ROC) curves. Results: Thirty patients (8.5%) developed VTE. Patients with VTE had significantly higher D‐dimer levels on admission ( P  = 0.045) and peak D‐dimer levels ( P  < 0.0001), in addition to higher rates of vasopressor requirements ( P  = 0.038), intubation ( P  = 0.003), and death ( P  = 0.023). Age (OR 1.042), obstructive sleep apnea (OR 5.107), and need for intubation (OR 3.796) were associated with significantly increased odds of VTE. Peak D‐dimer level was a good predictor of VTE (AUC 0.806, P  < 0.0001) and a D‐dimer cutoff of >6640 ng/mL had high (>70%) sensitivity and specificity for VTE. Conclusion: Peak D‐dimer level may be the most reliable clinical marker in COVID‐19 patients for predicting VTE and future prospective studies should attempt to further validate this.